Intelligent detection of untrusted data transmission to optimize energy in sensor networks. Issue 3 (2nd April 2020) - Yuvaraj, D.; Sivaram, M.; Navaneetha Krishnan, S.
Abstract: Nowadays environmental conditions are monitored using distributed sensors that react to the environment conditions and send the collected data over wireless channels. Every sensor's availability on wireless sensor networks depend on the amount of energy exist for it to increase its life time. As electricity is always the necessity of life and the problem is the cost at which it is generated. This paves way, for the need of an intelligent detection of malicious or duplicate data during their transmission over wireless sensor networks. There are different possibilities for a data to be corrupted or duplicated. Thus leading to false decisions and incorrect responses, especially when it comes to human. In such cases, the effective sensor fusion technique to be used to correlate correct data's from different sources providing a proper response to the user, also saving the sensor node energy by reducing unnecessary data transmissions. This is done by combining many data's from different sources and taking an appropriate sensor fused decision.